2001
DOI: 10.1037/0735-7036.115.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Do big-brained animals play more? Comparative analyses of play and relative brain size in mammals.

Abstract: It has been hypothesized that play is more likely to be present in larger brained species. We tested this hypothesis in mammals using independent contrasts, a method that controls for phylogenetic relatedness. Comparisons across 15 orders revealed that the prevalence and complexity of play was significantly correlated with brain size, with larger brained orders having more playful species. Three orders, Rodentia, Marsupialia, and Primates, were used for within-order comparisons among species and, where possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 98 publications
(153 reference statements)
1
65
0
2
Order By: Relevance
“…Pesquisas atuais têm procurado identificar as origens evolutivas (Bekoff & Byers, 1998;Iwaniuk et al, 2001;Pellis & Iwaniuk, 1999, 2000 e as funções ontogenéticas (Spinka et al, 2001;van der Berg et al, 1999) da brincadeira em animais de um modo geral e, de roedores, de modo particular.…”
Section: Conclusãounclassified
See 1 more Smart Citation
“…Pesquisas atuais têm procurado identificar as origens evolutivas (Bekoff & Byers, 1998;Iwaniuk et al, 2001;Pellis & Iwaniuk, 1999, 2000 e as funções ontogenéticas (Spinka et al, 2001;van der Berg et al, 1999) da brincadeira em animais de um modo geral e, de roedores, de modo particular.…”
Section: Conclusãounclassified
“…Em termos históricos, constata-se que houve grandes oscilações na publicação de artigos sobre brincadeira em roedores nas últimas três décadas. Através da análise da base de dados PsycINFO de 1970 até 2001, constata-se Análise motivacional, causal e funcional da brincadeira em duas espécies de roedores que as décadas de 80 e 90 foram bastante profícuas no estudo do comportamento lúdico em hamsters dourados e, principalmente, ratos albinos [esses roedores são os mais estudados em laboratório com relação ao estudo da brincadeira (Hole & Einon, 1984;Vieira, 1995) e que apresentam os índices mais elevados de complexidade de brincadeira social, que inclui ataque, defesa, contra-ataque e perseguição, por exemplo (Iwaniuk, Nelson & Pellis, 2001)]. Num total de 140 artigos, cerca de 90% destes foram publicados entre 1980 e 1999.…”
unclassified
“…Similarly, Byers (1999) reports a positive correlation between relative brain mass and frequency of social play in Australian marsupials. Iwaniuk et al (2001), however, found a play-brain size relationship between orders of mammals, but not within lower taxonomic groups, including primates and marsupials. Other research has shown that amygdala size predicts sexual adult-adult play in primates (Pellis & Iwaniuk 2002), and that amygdala and hypothalamus size are both positively related to all kinds of social play in non-human primates (Lewis & Barton 2006).…”
Section: Play and The Social Brainmentioning
confidence: 99%
“…Among birds, he found play in corvids and parrots. From a comparative analysis of mammals, it is possible to deduce a positive correlation between the intensity of play and the Encephalization Quotient (Iwaniuk, Nelson, and Pellis, 2001). Although neither clear-cut nor present within individual orders, this relationship is evident from the between-order analysis.…”
Section: The Basic Differences Between Play and Explorationmentioning
confidence: 99%
“…There is some initial data on play in some invertebrates (Mather and Anderson, 1999). Undoubtedly, the number of animal species in which play remains an important component of behavior in maturity is relatively small, and includes mostly animals with a high Encephalization Quotient (Iwaniuk, Nelson and Pellis, 2001).…”
Section: The Basic Differences Between Play and Explorationmentioning
confidence: 99%